Conflict Management and Employee Productivity in the Provision of Health Services: A Case Study of Mukongoro Health Centre III - Gladys Dorcas Ogwang (Uganda Christian University, 2025)
This research report was undertaken to investigate conflict management and employee productivity in the provision of health services. It was guided by three objectives; to find out the effect of communication strategies on employee productivity of health services at Mukongoro health center III, to find out the effect of leadership style on employee productivity of health services at Mukongoro health center III, to influence of resource allocation on employee productivity in the provision of health services at Mukongoro health center III. The researcher used a sample size of 63 respondents then used questionnaires and interview guide to collect data which was later analyzed using the statistical package for social sciences. Results of the first objective shows that communication strategies have a significant effect on employee productivity of health services at Mukongoro health center III, Supported by the following responses; 54% of the respondents were positive to the statement that clear communication reduces errors, which allows health workers to serve patients more efficiently and avoid repeated tasks; 62% were positive to the statement that patient-centered communication increases satisfaction, making employees feel more appreciated and committed to their work. Results of the second objective showed that leadership style has a significant effect on employee productivity of health services at Mukongoro health center III and was supported by the following responses which include; 80% of the respondents were positive to the statement that autocratic leadership can cause stress, which may lower employee performance and delay patient care, it can be observed that 57% were positive to the statement that transformational leadership inspires innovation, leading to better methods of delivering health services while results of the third objective indicated that resource allocation has a significant effect on employee productivity in the provision of health services at Mukongoro health center III. 60% forming the majority disagreed to the statement that adequate medical supplies help staff work faster, ensuring timely treatment for patients There is need for the government to prioritize leadership development within the health sector by investing in structured training programs tailored to different health service levels. The government should ensure that leaders in health institutions are not appointed based solely on academic qualifications, but also on proven leadership abilities and interpersonal skills.